Perspectives on spiritual intelligence - Dorobantu, Marius; Watts, Fraser N. (Routledge science and religion series, 2025)
The topic of intelligence involves questions that cut deep into ultimate concerns and human identity, and the study of intelligence is ideal ground for dialogue between science and religion.